Informação fluida e conhecimento no ciberespaço : uma análise do Portal Infonet-SE - Andrade, Polyana Bittencourt (2010)
The internet is a transbordering and potentializing environment for the information, since it makes possible the sheering, distribution and interaction of the contents available in it. However, this information system may generate an opposing move when it produces an avalanche of superficial information which difficult the absorption criticism by the user. This modern-liquid society, which is characterized by short living fashionisms, creates a fluid subject on which its habits do not become concrete, since they are so temporary that they don t shape up. The information also reproduces the same scenario, since the user is inserted into a logic based on supplying information and so it is conditioned to consume, not absorb or transform them into knowledge, since the flow of content production does not allow it. It is in his context that the publishing of cultural expressions come to be questioned, since they follow a liquid society trend. This discussion will take on topics that approach diverse cultural expressions in Sergipe, such as cinema, theater, craftsmanship, events, memory spaces(museums, art galleries, memorials, files, libraries, history institutes, science academies), amongst others and will analyze the content production of the Infonet Portal, from the reports published during April, May and June of 2008, period considered to be of cultural turbulence in the state, due to the June Festivals (Saint john, Saint Joseph and Saint Peter). To do so, Zigmunt Bauman s, Pierre Levy s, Edgar Morin s and Dominique Wolton s ideas were discussed. Besides, were analyzed the characteristics of the internet and its applicability within the portal hereby discussed in order to perceive the way the information is produced in the cyber culture, a movement that allows memorization, potentialization, interaction , besides other criteria inherent to the cyberspace